Learning method comparison between small-group discussion (SGD) and conventional to the knowledge improvement of midwifery department students - Iik Nurul Ulfah; Rara D.A.S.S Dethan; Friska Realita; Hanifatur Rosyidah (Universitas Aisyiyah Yogyakarta, 2021)
In 2013, the graduate competence of the midwifery department that fit current job demand was only 15%. Knowledge is one of the aspects of midwifery education quality. Small-Group Discussion (SGD) is one of the forms of students centered learning (SCL) where students are demanded to solve problems through a small group discussion. The object of this study is to figure out a comparison of knowledge improvement through the use of SGD or conventional methods. The method used in the study is quantitative of experimental pre-posttest design. The researcher divides the sample into two groups, the experimental group (19) is given an SGD approach and the control group (19) is given a conventional course approach. Based on the Independent Sample T-test, the value of Sig. (2-tailed) is 0.006 (0.05). Hence, it can be concluded that there is a significant difference between the average score of students’ knowledge level in the SGD group and the conventional group. The SGD group appears to have a higher improvement of average score, which is from 6.3 to 8.1 while the average score of the conventional group is from 6.1 to 6.8. Hence, it is considered that the SGD learning method can improve knowledge of midwifery students and can be used as an effective alternative method to achieve a student-centered learning system for other midwifery institutions.